Computational methods and points for attention in absolute configuration determination - Zhu, Huajie; Wang, Yufang; Nafie, Laurence A. (Frontiers in Natural Products, 2023)
With the rapid development of high performance computers and computational methods, including software, an increasing number of experimental chemists have tried to use computational methods such as optical rotation (OR, including the matrix model), optical rotatory dispersion (ORD), electronic circular dichroism (ECD or CD), vibrational circular dichroism (VCD), and magnetic shielding constants—nuclear magnetic resonance (NMR)—to explain and/or assign absolute configuration (AC) for various compounds. Such reports in the field of natural products have increased dramatically. However, every method has its range of application. This leads, in some cases, to incorrect conclusions by researchers who are not familiar with these methods. In this review, we provide experimental chemists and researchers with more computational details and suitable suggestions, and especially hope that this experience may help readers avoid computational pitfalls. Finally, we discuss the use of simplified models to replace original complex structures with a long side chain. The fundamental basis for using models to represent complex chiral compounds, such as in OR calculations, is the existence of conformation pairs with near canceling conformer contributions that justify the use of models rather than the original compounds. Using examples, we here introduce the transition state (TS) calculation, which may benefit readers in this area for use and mastery for their AC study. This review will summarize the general concepts involved in the study of AC determinations.